A convex decentralized optimization for environmental-economic power and gas system considering diversified emission control. (15th April 2019) - Qu, Kaiping; Shi, Shouyuan; Yu, Tao; Wang, Wenrui
Highlights: A novel environmental-economic dispatch of IPGS is established. A spatial and temporal diffusion control for air pollutants is constructed. A two-layer convex decentralized optimization PCCP-ADMM is proposed. The diffusion control effectively mitigates the harm of air pollutant emissions. PCCP-ADMM achieves a nearly global optimality with a fast convergence. Abstract: To mitigate two major environmental concerns of global warming and air pollution, natural gas power generation is growing in power supply, which makes power and natural gas system increasingly integrated. In this work, an environmental-economic dispatch incorporating diversified emission control is established for integrated power and gas system (IPGS). The traditional emission amount control for carbon emissions is adopted in IPGS, while a novel spatial and temporal diffusion control concerning ground concentration and spatial environmental protection requirements is proposed for air pollutant emissions. Furthermore, in view of information sharing difficulties between power and gas system, this paper proposes a novel two-layer convex decentralized optimization for the issue. The upper layer handles the nonconvex gas flow transmission with penalty convex-concave procedure based convexification. The lower layer solves each step of upper layer convexification with alternating direction method of multipliers based decentralized optimization, such that the information privacy of these two sub-systems is protected. Finally, simulation studies on two test systems validate the superiority of spatial and temporal diffusion control in reducing the air pollutant concentration, as well as the nearly global optimality and convergence efficiency of the two-layer method.